INNOVATION IN HUMAN RESOURCE MANAGEMENT: A SUSTAINABLE APPROACH FOR MICRO, SMALL, AND MEDIUM ENTERPRISES - Mistina, Rahayu Septyaning; Sulistyanto, Tri Hadi; Tampubolon, Irianty; Maruanaya, Yan; Dharsono, Wardhana W. (International Journal of Multidisciplinary Research and Literature, 2025)
This study analyzes the role of Human Resource Management (HRM) in supporting sustainability within Micro, Small, and Medium Enterprises (MSMEs). Through a comprehensive literature review of publications from 2020-2024, the research explores sustainable HRM practices including training, green leadership, and performance management systems. Utilizing Publish or Perish and VOSviewer software, the study identifies key themes and conceptual relationships in the literature. Findings reveal that sustainable HRM practices significantly contribute to human resource optimization and business sustainability. VOSviewer mapping uncovered relationships between HRM innovation, sustainable development, and MSME sustainability. The research highlights the importance of job training and visionary HRM approaches in supporting sustainable transformation. This study provides critical insights into the strategic role of HRM in achieving organizational sustainability